Supportive Organizational Environment dan Team Learning Capability sebagai Prediktor Self-Efficacy Mahasiswa Gen Z yang Berorganisasi di Kampus - Radina; Meliya Ashema Mahdina; Tisya Amanda; Siti Maisyarah; Muhammad Bayu Buana Fahmi; Shanty Komalasari (Universitas Negeri Malang, 2026)
Generation Z students who are active in campus organizations often face dual challenges, namely balancing high academic demands with heavy organizational responsibilities. This challenging condition demands a robust sense of self-efficacy for them to cope effectively. Therefore, this study explores the determinants of self-efficacy among Generation Z students who are actively involved in student organizations. This quantitative study specifically aims to analyze and empirically test the influence of a supportive organizational environment and team learning capability on students' self-efficacy levels. Data collection was conducted through a survey using questionnaires distributed to 103 participants, who serve as board members of executive organizations at UIN Antasari Banjarmasin. The gathered data were statistically analyzed employing multiple linear regression techniques. Simultaneous testing results demonstrate that a supportive organizational environment and team learning capability collectively exert a significant impact on self-efficacy. Nevertheless, partial testing outcomes indicate that neither variable possesses a meaningful independent influence when operating alone. These findings emphasize that fostering student self-efficacy fundamentally necessitates an inseparable synergy between positive environmental support and collaborative team learning processes. Abstrak Generasi Z yang aktif berorganisasi di kampus sering kali dihadapkan pada tantangan ganda, yakni menyeimbangkan tingginya beban tuntutan akademik dengan padatnya tanggung jawab organisasional. Kondisi ini menuntut adanya keyakinan diri yang kuat agar mereka mampu bertahan. Oleh karena itu, penelitian ini mengeksplorasi determinan self-efficacy pada mahasiswa Generasi Z yang terlibat aktif dalam organisasi kemahasiswaan. Studi kuantitatif ini secara khusus bertujuan untuk menganalisis dan menguji secara empiris pengaruh supportive organizational environment dan team learning capability terhadap tingkat self-efficacy mahasiswa. Pengumpulan data dilakukan melalui survei menggunakan kuesioner kepada 103 partisipan, yang merupakan pengurus organisasi eksekutif di UIN Antasari Banjarmasin. Data yang terkumpul dianalisis secara statistik menggunakan teknik regresi linear berganda. Hasil pengujian secara simultan membuktikan bahwa supportive organizational environment dan team learning capability secara bersama-sama memberikan pengaruh signifikan terhadap self-efficacy. Namun demikian, hasil uji parsial mengindikasikan bahwa kedua variabel tersebut tidak memiliki pengaruh yang bermakna ketika beroperasi secara mandiri. Temuan ini menegaskan bahwa pengembangan self-efficacy mahasiswa sangat membutuhkan sinergi yang utuh dan tak terpisahkan antara dukungan lingkungan organisasi yang positif dengan kolaborasi belajar di dalam tim.